Spatial Variations in Microfiber Transport in a Transnational River Basin - Alexia Balla; Ahmed Mohsen; Gönczy Sándor; Генці Шандор; Kiss Tímea (MDPI, 2022)
Abstract. Five countries share the catchment of the Tisza River (Central Europe). In most households electricity and water are available, and by washing synthetic clothes they can produce a large number of microfibers. However, in many sub-catchments of the river, the wastewater treatment is insufficient; therefore, microplastics (MP), especially plastic microfiber emissions into rivers, represent a problem. Our goal was to analyze the suspended sediment and microfiber transport at the low stage, making repeated (2021 and 2022) measurements in the Tisza River (946 km) at 26 sites across three countries. Water sampling was performed by pumping 1 m3 of water through sieves (90–200 µm). The mean MP transport in 2021 was 19 ± 13.6 items/m3, but it increased by 17% in 2022 (22.4 ± 14.8 items/m3). The most polluted sections were the Upper Tisza (Ukraine, Hungary) and the Lower Tisza (Serbia), where wastewater treatment is not satisfactory, whereas the Middle Tisza (Hungary) was less polluted. The tributaries increased the sediment and MP budget of the main river. Microfibers dominate (84–97%) the suspended MP transport, and thus it can be determined that they originated from wastewater. The MP transport was influenced by the availability of wastewater treatment plants, dams, tributaries, and mobilization of bottom sediments. At the low stage, no connection was found between the suspended sediment and MP particle transport.
Keywords: microplastic transport; reservoir; impoundment; tributary; bottom sediment; suspended sediment; wastewater management